SCN2A channelopathies: Mechanisms and models. (6th January 2020) - Hedrich, Ulrike B. S.; Lauxmann, Stephan; Lerche, Holger
Summary: Variants in the SCN2A gene, encoding the voltage‐gated sodium channel NaV 1.2, cause a variety of neuropsychiatric syndromes with different severity ranging from self‐limiting epilepsies with early onset to developmental and epileptic encephalopathy with early or late onset and intellectual disability (ID), as well as ID or autism without seizures. Functional analysis of channel defects demonstrated a genotype‐phenotype correlation and suggested effective treatment options for one group of affected patients carrying gain‐of‐function variants. Here, we sum up the functional mechanisms underlying different phenotypes of patients with SCN2A channelopathies and present currently available models that can help in understanding SCN2A ‐related disorders.